Kajian Pengelolaan Dana Koperasi Simpan Pinjam Pimpinan Koperasi Tunggal Ganda - Hasibuan, Abdul Ajis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In accordance with cooperative principles, management and is known as financial management, as well as functioning as intermediary management. The activities of the Savings and Loans Cooperative include collecting savings from the public, providing loans to the community, other cooperatives and/or the community, and managing funds and loans. This research was conducted at the Savings and Loans Cooperative Leaders of the Single Cooperative which is located at Jl. Relay No. 12 Lucky Field. Based on the results of the study it is known that Savings and Loans Cooperatives cannot rely on collecting funds from the public either in the form of savings, mandatory savings, time deposits. In addition, the Savings and Loans Cooperative is also less interested in establishing cooperation with other cooperatives either through bank programs or other programs. suboptimal. Weak regulations make the management of the Savings and Loans Cooperative act like a bank.